Exogenous vs. endogenous attention: Shifting the balance of fronto-parietal activity. (March 2018) - Meyer, Kristin N.; Du, Feng; Parks, Emily; Hopfinger, Joseph B.
Abstract: Despite behavioral and electrophysiological evidence for dissociations between endogenous (voluntary) and exogenous (reflexive) attention, fMRI results have yet to consistently and clearly differentiate neural activation patterns between these two types of attention. This study specifically aimed to determine whether activity in the dorsal fronto-parietal network differed between endogenous and exogenous conditions. Participants performed a visual discrimination task in endogenous and exogenous attention conditions while undergoing fMRI scanning. Analyses revealed robust and bilateral activation throughout the dorsal fronto-parietal network for each condition, in line with many previous results. In order to investigate possible differences in the balance of neural activity within this network with greater sensitivity, a priori regions of interest (ROIs) were selected for analysis, centered on the frontal eye fields (FEF) and intraparietal sulcus (IPS) regions identified in previous studies. The results revealed a significant interaction between region, condition, and hemisphere. Specifically, in the left hemisphere, frontal areas were more active than parietal areas, but only during endogenous attention. Activity in the right hemisphere, in contrast, remained relatively consistent for these regions across conditions. Analysis of this activity over time indicates that this left-hemispheric regional imbalance is present within the FEF early, at 3–6.5 s post-stimulus presentation, whereas a regional imbalance in the exogenous condition is not evident until 6.5–8 s post-stimulus presentation. Overall, our results provide new evidence that although the dorsal fronto-parietal network is indeed associated with both types of attentional orienting, regions of the network are differentially engaged over time and across hemispheres depending on the type of attention. Highlights: Adults performed endogenous and exogenous attention tasks during rapid-TR fMRI. Balance of frontal versus parietal activity differed between attention types. These differences in the fronto-parietal network were left-lateralized. Timing of fronto-parietal imbalances differed for voluntary and reflexive attention.